STRATEGIES OF PARENT–TEACHER PARTNERSHIP IN SUPPORTING INCLUSIVE ISLAMIC EDUCATION IN INDONESIA - Abdullah, Eramil Jantan (FORUM PAEDAGOGIK, 2025)
This study explores the strategies of parent–teacher partnership in supporting inclusive Islamic education in Indonesia. The main objective is to identify effective collaboration models that promote equal learning opportunities for students with diverse abilities in Islamic educational settings, particularly in inclusive madrasahs. Using a mixed-method approach, this research integrates both quantitative and qualitative data to obtain a more comprehensive understanding. Quantitative data were collected through questionnaires distributed to teachers and parents to measure levels of involvement, communication, and perceptions of inclusive practices, while qualitative data were obtained through in-depth interviews and classroom observations to understand experiences, challenges, and applied collaboration strategies. The findings reveal that effective communication, mutual respect, and shared commitment rooted in Islamic values are the key foundations for successful collaboration. Continuous dialogue between parents and teachers facilitates early identification of students’ needs and enables collaborative problem-solving. Islamic values such as sincerity (ikhlas), compassion (rahmah), and justice (‘adl) form the moral basis that strengthens inclusive practices. The contribution of this study lies in developing an Islamic values–based partnership model that can be implemented in inclusive madrasahs to enhance the effectiveness of parent–teacher collaboration. In addition, the research provides practical implications for policymakers and Islamic educational institutions in designing collaborative training programs oriented toward character education and diversity. In conclusion, strengthening parent–teacher partnerships not only improves students’ academic achievement but also fosters moral integrity, empathy, and spiritual awareness as essential foundations for shaping excellent Muslim generations in the era of disruption.